Fortalecimiento de la Política Pública de Seguridad Vial en el cantón Calvas, hacia una Comunidad Segura y Responsable en el Tránsito - Alverca Jiménez, Marco Vinicio (2024)
Traffic accidents are tragic events that result in loss of lives, severe injuries, and property damage. These incidents involve both vehicles and individuals, representing a persistent challenge in society. According to a report from the National Institute of Statistics and Census, in the first quarter of 2023, the primary cause of traffic accidents in the country was driver incompetence and recklessness, followed by disregard for traffic signals. To fulfil the main objective of this research, which focuses on identifying the primary causes of traffic accidents in the area, a descriptive methodology with a mixed approach was employed. This involved a thorough analysis of statistical data recorded by the National Traffic Agency on accidents in Calvas. Additionally, online focus groups were conducted, and semi-structured interviews were carried out with various participants. The results revealed that distracted driving caused 64% of traffic accidents in Calvas. Furthermore, 54% of fatalities in traffic accidents were attributed to loss of control and vehicles veering off the road. According to the survey findings, a significant percentage of the population is unfamiliar with the coordination and cooperation mechanisms for road safety in Calvas, with 40% being familiar, while 60% are not. Therefore, it can be concluded that strengthening the public policy for road safety in the canton requires a combination of educational, preventive, and control measures.